Original Sin, Preterition, and its Implications for Evangelization - Echeverria, Eduardo J. (2020)
In this paper, I examine the four elements—universal sinfulness, natural sinfulness, inherited sinfulness, and Adamic sinfulness—of the doctrine of original sin in both the Reformed confessions, with particular attention to the Canons of Dort, and the Council of Trent’s definitive teaching on Original Sin. I give particular attention to the question regarding how all men are implicated in the sin of Adam. Realism and federalism will be analyzed as answers to this question. Even if a theological account is given that justifies the claim that God may justly impute Adam’s sin to his posterity, that still leaves unanswered the question of unconditional negative reprobation, also called, preterition (praeteritio), namely, that God passes over some and not others. Does preterition jeopardize the Church’s call to evangelization? That question will need to be reconsidered briefly, and in conclusion, in light of the doctrine of divine election and its implications for the preaching and hence proclamation of the gospel.
Keywords: Original Sin; essential asymmetry; Federalism; preterition; Realism